A evolução histórica da formação do professor de 2. grau nas Faculdades de Educação ou unidades equivalentes - Semeraro, Vera Maria Soeiro (1977)
Education has been under serious, permanent, violent criticism to its productivity, effectiveness and efficiency. The systematic attack on schools, particularly those designed to train teachers, has been constant in Old-, Third- and New-World countries. Everyone agrees that the function of teaching requires professional competence, and that the latter's absence is mainly responsible for the gaps, insufficiencies and deficiencies of the educational process. The teaching-learning situation provided by a well-oriented didactical activity is believed to be a factor of paramount importance to the effectiveness and efficiency of an educational system. Having considered the expansion of high-school education. which made it lose a lot of its academical and selective character, it was chosen to study the training of the teacher being prepared for high-school teaching. In order to find out what king of training the high-school teacher has been receiving and the consequences of such a training to his professional performance,critical analysis was made of the historical evolution of teachers training in Brazil. A study was also performed of the curricula of the courses offered by Teacher Colleges and equivalent units in the State of Espírito Santo, been found that such colleges and schools have It has generally adopted the minimum curriculum proposed by the Federal Edu eation Couneil. It is known that high-school education is presently designed to students from all social classes, and that its objectives are now much wider than before; it has been found that the changes in curricula have been limited to useless increases or decreases subjects, in cless-hours and lt has been inferred that the Education College has not brought any significant innovation to the curricula of high-school-teachers pedagogical training. This confirms the negative criticism such training has been under. It is recommended that field research should be carried out and curricular proposais should be studied in order to obtain subsidy for reformulating present curricula.